1994
DOI: 10.1104/pp.105.2.681
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Boron in Cell Walls of Squash and Tobacco and Its Association with Pectin (Evidence for a Structural Role of Boron in the Cell Wall)

Abstract: B deficiency results in a rapid inhibition of plant growth, and yet the form and function of B in plants remains unclear. In this paper we provide evidence that B is chemically localized and strudurally important in the cell wall of plants. The localization and chemical fractionation of B was followed in squash plants (Curcurbifa pepo 1.) and cultured tobacco cells (Nicofiana fabacum) grown in Breplete or B-deficient medium. As squash plants and cultured tobacco cells became deficient, an increasingly large pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
170
1
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(188 citation statements)
references
References 11 publications
(18 reference statements)
11
170
1
6
Order By: Relevance
“…Furthermore, previous research in radish (Raphanus sativus) and squash (Curcurbita pepo L.) (Matoh et al 1993;Hu and Brown 1994) indicated that under low B condition, cell wall B represented most of cellular B. However, the results in the present study were not consistent with this (Table 3).…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…Furthermore, previous research in radish (Raphanus sativus) and squash (Curcurbita pepo L.) (Matoh et al 1993;Hu and Brown 1994) indicated that under low B condition, cell wall B represented most of cellular B. However, the results in the present study were not consistent with this (Table 3).…”
contrasting
confidence: 57%
“…The symptoms of B deficiency observed in this study could be attributed to the theory that B plays an important role in cell wall structure and plasticity (Hu and Brown 1994). Boron cross-links pectin in cell walls, and the cross-linking appeared to be essential for normal expansion of leaves (O'Neill et al 2001).…”
Section: Discussion Boron Deficiency and Toxicity In Plant Growthmentioning
confidence: 72%
See 1 more Smart Citation
“…Deficiency symptoms are noticed in the root apex within hours and within minutes in the pollen tube (Gupta, 1993;Dell & Huang, 1997). Limited retranslocation of B has been attributed to its low mobility in the phloem sap and its fixation in components of mature leaves (Hu & Brown, 1994;Shelp et al, 1995). However, species and genotypes that are less sensitive to B deficiency are able to retranslocate B from the more mature tissues (source) to younger tissues (sink) (Shelp, 1993;Shelp et al, 1995;Brown & Shelp, 1997;Perica et al, 2001) and this capacity of mobilizing and transporting B to tissues with a high demand could explain their lower sensitivity to B deficiency (Brown & Hu, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Das funções atualmente atribuídas ao B, duas são aceitas pela comunidade científica: uma é como constituinte da parede celular -nela, o B, possivelmente, atuaria estabilizando-a (Matoh et al, 1993;Hu & Brown, 1994;Ishii & Matsunaga, 1996;Kobayaski et al, 1996;Fleischer et al, 1998;Pfeffer et al, 2001); a outra função seria a manutenção da integridade da membrana plasmática (Cakmak et al, 1995).…”
Section: Introductionunclassified